The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1039/d0ra04853d
|View full text |Cite
|
Sign up to set email alerts
|

Nanocellulose–organic montmorillonite nanocomposite adsorbent for diuron removal from aqueous solution: optimization using response surface methodology

Abstract: CNCs and CTM were combined to obtain a nanocomposite used to remove diuron in water. The adsorption of the nanocomposite was analyzed using response surface methodology, isothermal adsorption model and adsorption kinetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…36 Diurion, a herbicide, was adsorbed by a nanocomposite prepared using CNCs/organic montmorillonite through hydrogen bonding and hydrophobicity of the alkyl groups. 37 Karim et al utilized CNCs in chitosan membranes cross-linked with glutaraldehyde for decontamination of water from rhodamine 6G, Victoria blue 2B, and methyl violet 2B. 38 Herein, microcrystalline cellulose (MCC) is exposed to sulfuric acid hydrolysis under a mild temperature condition of ∼45 °C for 2 h followed by dialysis and freeze-drying to obtain CNC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Diurion, a herbicide, was adsorbed by a nanocomposite prepared using CNCs/organic montmorillonite through hydrogen bonding and hydrophobicity of the alkyl groups. 37 Karim et al utilized CNCs in chitosan membranes cross-linked with glutaraldehyde for decontamination of water from rhodamine 6G, Victoria blue 2B, and methyl violet 2B. 38 Herein, microcrystalline cellulose (MCC) is exposed to sulfuric acid hydrolysis under a mild temperature condition of ∼45 °C for 2 h followed by dialysis and freeze-drying to obtain CNC.…”
Section: Introductionmentioning
confidence: 99%
“…In situ polycondensation was performed on CNCs with melamine formaldehyde by Grishkewich et al to remove MO . Diurion, a herbicide, was adsorbed by a nanocomposite prepared using CNCs/organic montmorillonite through hydrogen bonding and hydrophobicity of the alkyl groups . Karim et al utilized CNCs in chitosan membranes cross-linked with glutaraldehyde for decontamination of water from rhodamine 6G, Victoria blue 2B, and methyl violet 2B …”
Section: Introductionmentioning
confidence: 99%
“…For example, high cation exchange cetyltrimethylammonium bromide modified montmorillonite (CTM) has been used as an additive for CNC scaffold, where the composite was effective for adsorption of diurona potential carcinogenic herbicide. 452 Pristine CNC displayed a surface area of 27.23 m 2 /g, which was increased to 39.51 m 2 /g in CNC/CTM composite. It was found that around 70 mg/L of the composite was needed to adsorb 6.0 mg/L of diuron, which was below the permissible level of diuron in drinking water (100 mg/L) set by the US Environmental Protection Agency.…”
Section: Adsorptionmentioning
confidence: 92%
“…Some NC-based nanocomposites are found to be efficient to adsorb both organic and inorganic pollutants. For example, high cation exchange cetyltrimethylammonium bromide modified montmorillonite (CTM) has been used as an additive for CNC scaffold, where the composite was effective for adsorption of diurona potential carcinogenic herbicide . Pristine CNC displayed a surface area of 27.23 m 2 /g, which was increased to 39.51 m 2 /g in CNC/CTM composite.…”
Section: Nc-enabled Water Purification Technologiesmentioning
confidence: 99%
“…Likewise, Mautner et al (2017) demonstrated that the cationic cellulose nanopaper membranes are efficiently useful for the continuous removal of nitrates, released from the chemical fertilizer in the agriculture soil and irrigation water [108]. Similarly, several researches revealed that the nanocellulose can serve as a potential adsorbent for the removal of pesticides, such as chlorpyrifos [143], tetraconazole [144], diuron [145], organophosphorus [146], difenoconazole, and nitenpyram [147]. Nanocelluloses are also employed for the adsorption and elimination of hazardous drugs from industrial wastewater, such as ciprofloxacin, diclofenac [124], metronidazole [148], and ceftriaxone [149].…”
Section: Adsorbents For Hazardous Organic Pollutants Removalmentioning
confidence: 99%